PSIKOLOGI TOKOH MIYUKI DALAM NOVEL IKITEMASU, 15 SAI KARYA MIYUKI INOUE - Aimmatu Wicaksono, Tyas Ilmayuni (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The object in this research is "Ikitemasu, 15 Sai" which is written by Miyuki Inoue. This novel was selected because the main character has inferiority feeling and inner pressure, so she felt different with the others. The issue in this research has been focused on how the influence of heredity and environment factors in the formation of personality main character, and how the development psychology of main character based on individual psychology of Adler’s in the novel "Ikitemasu, 15 Sai". The theory used in this research is literature psychology by Wellek and Warren, heredity factor theory by Sujanto, environment factor theory by Patty, and theory of individual psychology by Adler. The analysis results showed that the existence of these factors gave birth to private Miyuki who have a high curiosity, daring, independent, confident, cheerful, and eager to live her life. Through this theory presented Miyuki struggles to be successful, with a lifestyle that has been formed since childhood, and social interests of the surrounding environment . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: premature, retinopathy of prematurity, blind children.